Diseño de estrategias comunicativas para la población de la Administración Zonal “Los Chillos” sobre prevención de incendios forestales. - González Villagómez, María Mercedes (2014)
Communication throughout history has evolved by leaps and bounds is so efficient that in seconds can transmit a message across the world; but what we send should be momentous, to change the view we have of things, this work aims to guide the population to a harmonious coexistence with the environment. The fires in the years 2012 - 2013 in summer, have the second leading cause agricultural burning is an ancient technique that has been developed over time, being the cheapest and fastest way to get rid of weeds and debris from previous crops, in order to pave the way for new planting. You must train people in techniques for proper controlled burning, because you can not ban them radically, rather it should prevent this is that better management of processes have to be used.